Development of IoT on Irrigation System for Garden - Mohd Atif Bin Mohd Yaziz; Syed Mohammed Uddin; Mohd Izhar A Bakar (Journal of Engineering Technology, 2022)
This system research aims to use a Raspberry Pi 3 to develop control and monitoring systems that will automatically sprinkle water on the garden to irrigate it. The soil moisture sensor will determine whether the soil is dry or wet. A user can use the Blynk app on their smartphone to keep an eye on the garden conditions while also employing the camera for direct surveillance by connecting to a Wi-Fi network. It’s important to avoid giving plants an uncontrollable amount of water and avoid water waste, especially in agriculture. Two gardens have been used to test two different irrigation systems: A uses an Internet of Things (IoT) irrigation system, while B uses a regular irrigation system. The results reveal that Garden B’s irrigation procedure consumes a lot of water in just 14 days, whereas Garden A’s conditions show improvement over time when compared to traditional irrigation methods. Therefore, compared to the previous system, this design is more effective at controlling the watering process and keeping an eye on the Garden. It would be better if the existing irrigation system had a Raspberry Pi Touch LCD Display, using renewable energy as a backup power source during power outages, and employing high-pressure water pumps to cover a large area of the garden.